Flexible work practices: Perspectives from the southern hemisphere - Frank M. Horwitz; Cameron Allan; Peter Brosnan; Pat Walsh (South African Journal of Business Management, 2000)
Labour market flexibility continues to be important for employers seeking to improve productivity, reduce costs and be competitively agile. But it also carries downside costs for employees of increased insecurity, potentially deteriorating employment standards and lower morale. In this article numerical and temporal types of flexibility are considered in an analysis of three southern hemisphere countries.